Outcomes of Hypofractionated Stereotactic Radiotherapy for Small and Moderate-Sized Brain Metastases: A Single-Institution Analysis - Yan, Michael; Zalay, Osbert; Kennedy, Thomas; Owen, Timothy E.; Purzner, James; Taslimi, Shervin; Purzner, Teresa; Alkins, Ryan; Moideen, Nikitha; Fung, Andrea S.; Moraes, Fabio Y. (Frontiers in Oncology, 2022)
Background: Stereotactic radiosurgery (SRS) is the standard treatment for limited intracranial metastases. With the advent of frameless treatment delivery, fractionated SRS (FSRT) has become more commonly implemented given superior control and toxicity rates for larger lesions. We reviewed our institutional experience of FSRT to brain metastases without size restriction. Methods: We performed a retrospective review of our institutional database of patients treated with FSRT for brain metastases. Clinical and dosimetric details were abstracted. All patients were treated in 3 or 5 fractions using LINAC-based FSRT, did not receive prior cranial radiotherapy, and had at least 6 months of MRI followup. Overall survival was estimated using the Kaplan Meier method. Local failure and radionecrosis cumulative incidence rates were estimated using a competing risks model with death as the competing risk. Univariable and multivariable analyses using Fine and Gray’s proportional subdistribution hazards regression model was performed to determine covariates predictive of local failure and radionecrosis. Results: We identified 60 patients and 133 brain metastases treated at our institution from 2016-2020. The most common histologies were lung (53%) and melanoma (25%). Most lesions were >1cm in diameter (84.2%) and did not have previous surgical resection (88%). The median duration of imaging followup was 9.8 months. The median survival for the whole cohort was 20.5 months. The local failure at 12 months was 17.8% for all lesions, 22.1% for lesions >1cm, and 13.7% for lesions ≤1cm (p = 0.36). The risk of radionecrosis at 12 months was 7.1% for all lesions, 13.2% for lesions >1cm, and 3.2% for lesions ≤1cm (p = 0.15). Conclusions: FSRT is safe and effective in the treatment of brain metastases of any size with excellent local control and toxicity outcomes. Prospective evaluation against single fraction SRS is warranted for all lesion sizes.